RECOVERY OF CANINE OOCYTES BY SLICING METHOD - UMAMAGESWARl, J; JOSEPH, CECILIA; KULASEKAR, K; BALASUBRAMANIAN, S; SRIDEVl, P (The Indian Journal of Animal Reproduction, 2023)
Ovaries were collected from bitches undergoing routine ovario-hysterectomy and transported in physiologicalsaline at 35°C to 38°C within 2 to 3 h of collection. A total of 1616 oocytes were retrieved by slicing of 52 ovarieswith a recovery rate of 31.07 ± 3.47 oocytes per ovary. Among the collected oocytes 25.93, 43.07 and 31.00percent of oocytes were graded as I, II and Ill respectively. The overall good quality oocytes (grade I and II COCs)recovered from bitch ovaries by slicing method irrespective of reproductive cycle in the present study was 69.00percent.
Keywords: Ovaries; Bitch; Oocyte; Recovery